Preventing Corruption in Bali’s Customary Villages: How Do Regional Institutions Play a Role? - Rejeki, Ni Komang Windu; Dwi Atmaja, Bima Kumara; Krisna Yanti, Anak Agung Istri Eka (Udayana Journal of Law and Culture, 2024)
Customary villages are traditional institutions in Bali that have existed for centuries. The village has autonomy when it comes to managing its customary arrangements based on local traditions and wisdom, meaning that it does not have a hierarchical relationship with the government based on the state structure of the Republic of Indonesia. The Bali Province Government, a second-layer hierarchical government structure in Indonesia, applies a unique approach to performing relationships with customary villages in Bali as it has regularly supported the existence and activities of customary villages, including providing funding assistance. Unfortunately, several cases have shown the misuse of government funds. This article, therefore, identifies the practice of fraud and corruption in customary villages in Bali. Second, it analyses the role of the Customary Community Development Agency (DPMA) of the Bali Province Government in supervising the financial management of Bali's customary villages. Lastly, it supports the synergy between DPMA and the Representative Office of the Financial and Development Supervisory Agency (BPKP) of Bali Province in preventing corruption cases in the customary villages . The article applies empirical legal research, which involves collecting primary and secondary data and analyzing them using statutory, factual, and legal concept analysis approaches. The research suggests that fraud and corruption cases in customary villages cause a loss of government funds, harming the financial management of Village Credit Institutions (LPD), and involving the misuse of power. The provincial regulation authorizes DPMA to address this issue by monitoring how customary villages use the Bali Province Government grants. This paper then argues that the DPMA’s role would be more effective if it adopted a more formal collaboration with the Representative BPKP in Bali Province through various joint programs that support the comprehensive efforts to prevent corruption in customary villages in Bali.